2021
DOI: 10.1111/ijcs.12681
|View full text |Cite
|
Sign up to set email alerts
|

Life insurance purchase behaviour: A systematic review and directions for future research

Abstract: This paper presents a framework-based systematic review of existing research to understand the purchase behaviour of consumers for life insurance products. The TCM framework is adopted to provide an organized review of the theory, context and methods used in the articles under review. Antecedents, decisions and outcomes in the context of consumers' life insurance purchase behaviour are also discussed in detail using the ADO framework. The review aggregates 136 unique antecedents derived from 76 relevant articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 128 publications
(293 reference statements)
0
27
0
Order By: Relevance
“…Other systematic literature reviews that form an extended part of the inaugural special issue (i.e., reviews that were submitted around a similar time under the regular “review” category) that will be worthwhile exploring include Bhatia et al. 's (2021) review on life insurance purchase behavior, Cavalinhos et al. 's (2021) review on in‐store mobile device usage, Goyal and Kumar's (2021) review on financial literacy, Kapoor and Banerjee's (2021) review on brand scandal, Mamun et al's (2021) review on Islamic marketing, Mishra et al.…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…Other systematic literature reviews that form an extended part of the inaugural special issue (i.e., reviews that were submitted around a similar time under the regular “review” category) that will be worthwhile exploring include Bhatia et al. 's (2021) review on life insurance purchase behavior, Cavalinhos et al. 's (2021) review on in‐store mobile device usage, Goyal and Kumar's (2021) review on financial literacy, Kapoor and Banerjee's (2021) review on brand scandal, Mamun et al's (2021) review on Islamic marketing, Mishra et al.…”
Section: Exemplars Of Systematic Literature Reviewsmentioning
confidence: 99%
“…Outcomes signify the consumers’ behavioral responses (Bhatia et al , 2021). Our study found four significant outcomes: repurchase intention, purchase decision, loyalty and WOM.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this will help identify themes to halal cosmetics consumption antecedents, decisions and outcomes (ADO). According to Bhatia et al (2021), the integration of TMC and ADO enables scholars to analyze the structure and offers much more explicit future directions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent research paper by Bhatia et al. (2021a, b) analysed the theories of traditional finance and behavioural finance that are generated based on behavioural aspects.…”
Section: Literature Reviewmentioning
confidence: 99%